Sosialisasi dan Pemanfaatan Data Antropometri Murid di SD Global Mandiri Cibubur untuk Tinjauan Ergonomi Meja dan Kursi - Yanto, Yanto; Surbakti, Feliks Prasepta Sejahtera; Suprata, Ferdian; Prasetya, Wibawa; Salsabila, Syafira (Jurnal Pengabdian Masyarakat Charitas, 2021)
The activity aimed to help school to determine whether the schoolfurniture which were provided to the students match with theirdimensions. The evaluation focused on students from Grade 1-3. Byusing ergonomics criteria and students’ anthropometry, the chair anddesk were evaluated. Results showed that most students’ did not matchwith the chair available to them. The height of chair were too high forthe majority of students with percentage are ranging from 12.5% (Boysin Grade 3) to 87.5% (Girls in Grade 1). Meanwhile, the height of deskwas not appropriate for all students from Grade 1 to Grade 3 (100%percentage). Findings from this activity suggested that the schoolauthority should evaluate the used of their school furniture.